Haliclystus californiensis, a “new” species of stauromedusa (Cnidaria: Staurozoa) from the northeast Pacific, with a key to the species of Haliclystus - Kahn, Amanda S.; Matsumoto, George I.; Hirano, Yayoi M.; Collins, Allen G. (Zootaxa, 2010)
We describe Haliclystus californiensis, a new species of stauromedusa from the northeast Pacific. Haliclystus californiensis differs from other species within the genus primarily by its horseshoe-shaped anchors, but also by the presence of prominent glandular pads at the base of its outermost secondary tentacles and by geographic range. It has been found from southern to northern California in coastal waters, 10 to 30 m depth. A single specimen of the species was originally described in an unpublished dissertation; nine additional specimens have been found since that time. We provide an annotated key to the known species of Haliclystus.